(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
Insufficient motor activity of primary school students is the cause of a decrease in the functional capabilities of the cardiorespiratory system of students, which is manifested by an inadequate response of the heart to physical exertion and a decrease in the vital capacity of the lungs. Therefore, the main task of modern society is to find ways to increase the level of physical fitness of schoolchildren. Some authors suggest using swimming. So, the purpose of the study was to determine the level of physical fitness of primary school students who are engaged in swimming. The study involved 45 students aged 6-10 who are engaged in swimming. We tested the physical fitness of students in grades 1-4 using the following tests: 30m run, 4x9m shuttle run, long jump from a standing position, hanging on a crossbar with bent arms, raising the torso to a sitting position for 1 minute, forward torso tilt, and dynamometry. The results of our study showed that the average values of static strength, speed, and explosive strength are higher in girls and boys in grades 2, 3, and 4 than the average values of the above-mentioned indicators in first-graders. In addition, we registered gender differences in the improvement of the average values of such indicators as flexibility and agility. They are higher in girls. The average values of handgrip dynamometry indicate uneven development of strength in younger schoolchildren. Thus, we found a decline in this physical quality in third-graders.